Optiques : The Science of the Eye and the Birth of Modern French Fiction - Goulet, Andrea (Book collections on Project MUSE., 2006)
Andrea Goulet takes the study of the novel into the realm of the visual by situating it in the context of nineteenth-century scientific and philosophical discourse about the nature of sight. She argues that French realism, detective fiction, science fiction, and literature of the fantastic from 1830 to 1910 reflected competition between two modern visual modes: a not-yet-outdated idealism and an empiricism that located truth in the body. More specifically, the book argues that key narrative forms of the nineteenth century were shaped by a set of scientific debates: between idealism and materialism in Honor Balzac's Comdie humaine, between deduction and induction in early French detective fiction, and between objective vision and subjective vision in the "optogram" fictions of Jules Verne and others. Goulet aims to revise critical views on the modern novel in a number of ways. For instance, although many literary studies focus on the impact of cinema, photography, and painting, Optiques asserts the materialist bases of realism by establishing a genealogy of popular fictional genres as fundamentally optical, that is, as articulated according to bodily notions of sight. With its chronological and interdisciplinary scope, Optiques stands to contribute an important chapter to the study of literary modernity in its scientific context.